Upgrading of fast pyrolysis bio-oil to drop-in fuel over Ru catalysts. Issue 4 (August 2019) - Ma, Zhongyi; Wei, Lin; Zhou, Wei; Jia, Litao; Hou, Bo; Li, Debao; Zhao, Yongxiang
Abstract: Catalyst plays a key role in the upgrading of fast pyrolysis bio-oil to advanced drop-in fuel, while the selectivity and deactivation of catalyst still remain the biggest challenge. In this study, three Ru catalysts with activated carbon, Al2 O3 and ZSM-5 as supports were prepared and tested in bio-oil hydrotreating process. The physical properties and components of upgraded bio-oil were detected to identify the difference in catalytic performance of three catalysts. The results showed that furan, phenols and their derivatives in fast pyrolysis bio-oil could be hydrogenated to alkanes, alkenes and benzenes over Ru catalysts. The different components of oil phase over three catalysts may be resulted from the surface properties of three supports. Activated carbon supported Ru catalyst showed the best catalytic performance and was suggested to be the most promising catalyst for pyrolysis bio-oil upgrading. Highlights: Furan, phenols and their derivatives could be hydrogenated to alkanes, alkenes and benzenes over Ru catalysts. The different components of oil phase over three catalysts may be resulted from the surface properties of supports. Activated carbon supported Ru catalyst showed the best catalytic performance for bio-oil upgrading.